Implementation of a Rule-Based Decision Support System in Determining the Level of Customer Satisfaction with Services - Kerry Buck Manulak; Shaiful; Wisda; Mandeine Resyi (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
Sarmi Car Wash is a car and motorbike washing service located at Jalan Sultan Hasanuddin No. 52, offering pick-up and drop-off services within a specified range. To enhance employee performance and customer service, the business seeks to implement a decision support system (DSS) to monitor employee performance and assess customer satisfaction effectively. This research aims to design a web-based DSS application that utilizes rule-based assessments of employee performance, integrating data such as employee names and tenure as references for developing the system. The study employed data collection methods including observation, interviews, documentation, and literature review. The system was tested using the black-box method, confirming that it functions as intended. Additionally, based on a user assessment questionnaire, the application achieved an average score of 80.4%, indicating its suitability and effectiveness for implementation. The developed system provides an efficient solution for improving service quality and employee performance monitoring at Sarmi Car Wash.